What Happens After the Court of Justice Has Given its Ruling? Promises and Pitfalls of Strategic Litigation Against Internal Border Controls in EU Law - Stefan Salomon (German Law Journal)
This Article inquires into the aftermath of judgments by the CJEU under the preliminary ruling procedure under article 267 TFEU in cases of strategic litigation. As the principal objective of strategic litigants is to effectively achieve broader societal, political, economic, or legal change, the afterlife of a judgment is crucial for them. While excellent scholarship exists on strategic litigation in EU law, much remains unclear on what happens to a case after the Court of Justice of the EU (CJEU) has given its judgment. Does the referring court and other national courts faithfully comply with the judgment of the CJEU? Do governments implement the ruling? This Article takes the decision of the CJEU in Landespolizeidirektion Steiermark, which concerns the reintroduction of internal border controls, as case study to inquire into the different factors that affect the implementation of a preliminary ruling that is the outcome of strategic litigation. The main argument in this Article is that the implementation of preliminary rulings is determined by the interplay between three different factors: The role of strategic litigants to initiate follow-up litigation, the receptivity of national courts to comply with a preliminary ruling, and the European Commission’s willingness to enforce a preliminary ruling.